Pedagogical Competencies in The Prescribed and Enacted Curriculum for Graduate Students - Tondoprasetyo, Fransisca Kristanti (Beyond Words, 2021)
TThis case study is aimed to find out far the curriculum in a teacher education institute has integrated these pedagogical competencies in both their prescribed and enacted curriculum using the Actor Network Theory (ANT). ANT is applied in this research to see the network formed in both the prescribed and enacted curriculum so as to find out how students master the pedagogical competencies in the coursenet of three investigated courses, namely Principles of English Language Teaching, Teaching Reading and Writing, and Teaching Listening and Speaking. Therefore, this research analyzes how the human and nonhuman entities influence each other in both prescribed and enacted curriculum in two perspectives: 1) to what extent are the pedagogical competencies intended for graduate students in TEFL program? 2) to what extent are the pedagogical competencies delivered to the graduate students in TEFL program?  The result of the study shows that most pedagogical competencies are delivered in the three investigated courses. Lecturers and students are human entities in the network formed in the courses while the nonhuman entities involved within the network are noises, light, class settings, and class location. Lecturers then become key actors that impact upon the actants–students– to act upon the translation process to master the pedagogical competencies. As for the non-human entities, they influence the learning atmosphere in which graduate students in TEFL are situated as they learn to master the pedagogical competencies. The coursenet formed within the three investigated courses have shown that evaluation and improvement need to be done by the education institution to enhance the quality of teachers’ education curriculum